Efficacy and safety of acupuncture on sleep quality for post-stroke insomnia: a systematic review and meta-analysis - Shi, Menglong; Ji, Zhaochen; Sun, Tianye; Hu, Haiyin; Chen, Zhe; Feng, Chaonan; Zhang, Junhua; Zhao, Min; Yang, Fengwen (Frontiers in Neurology, 2023)
Stroke is the second leading cause of death worldwide, and improving sleep quality in post-stroke insomnia is beneficial to the recovery of stroke. Acupuncture is widely used for the treatment of post-stroke insomnia in China. Therefore, this systematic review and meta-analysis were performed to explore the efficacy and safety of acupuncture for post-stroke insomnia. Eight databases were searched from their inception to 12 September 2022. Two reviewers independently performed the study screening and data extraction. The outcomes include Pittsburgh Sleep Quality Index (PSQI), objective sleep data measured by polysomnography (PSG), long-term efficacy and adverse events. The quality of the trials was assessed by the Cochrane risk of bias tool 2.0. The RevMan 5.4 and Stata 15.1 were used for data synthesis. Among 3233 participants from 41 studies were included. Pooled results indicated that acupuncture was superior to control group (CG) in improving PSQI total score (standardized mean difference (SMD) = -1.03, 95% confidence interval (CI): -1.32, –0.74, P < 0.00001), increasing sleep efficiency (SMD = 0.65, 95% CI: 0.37 to 0.92) and total sleep time (SMD = 0.54, 95% CI: 0.22 to 0.86). The favorable results in improving PSQI total score (SMD = 0.65, 95% CI: 0.37 to 0.92), reduced sleep latency (SMD = 1.84, 95% CI: 0.31 to 3.38) and increased total sleep time (SMD = -0.73, 95% CI: -1.15 to -0.31) were also observed in comparisons of acupuncture plus CG vs. CG. As of long-term efficacy and safety, the effects of acupuncture were long-term and robustness, however, due to limited safety information, reliable safety conclusions cannot be drawn. Subgroup analysis showed that acupuncture plus CG was superior to CG for post-infarction patients, but the efficacy of acupuncture alone compared to non-BZDs or other hypnotics needs further research. The GRADE assessment demonstrated that the level of evidence was mostly low or very low given the flaws in the study design and considerable heterogeneity among the included studies. Acupuncture could improve sleep quality, has long-term efficacy and without serious adverse events. However, the findings should be treated with caution owing to the existence of methodological quality issues.